New Records of Phenacoccus solenopsis Natural Enemies in Europe and Taxonomic Additions on Anagyrus matritensis - Michele Ricupero; Emanuele Porcu; Agatino Russo; Lucia Zappalà; Gaetano Siscaro (Insects)
The cotton mealybug Phenacoccus solenopsis (Hemiptera: Pseudococcidae) is a polyphagous invasive species native to America and considered one of the major cotton pests in Asia. It is currently threatening horticultural and ornamental protected crops in Mediterranean countries. Due to ecological and environmental concerns, the conventional chemical control of P. solenopsis in new areas of introduction is being replaced by exploring the potential of indigenous natural enemies as a sustainable biological control tool. After P. solenopsis introduction in Sicily (Italy), field surveys were conducted on native natural enemies attacking the mealybug to select promising biocontrol agents for field applications. For the first time, Aenasius arizonensis (Hymenoptera: Encyrtidae) was reported in Europe, and the native Anagyrus matritensis (Hymenoptera: Encyrtidae) was recorded in association with P. solenopsis. The two parasitoid species were identified by morphological features and molecularly using a portion of the mitochondrial cytochrome oxidase subunit I (mtCOI) gene. Because of missing information, additional morphological features were provided for the morphological identification of A. matritensis. In addition, the generalist predators Cryptolaemus montrouzieri, Hippodamia variegata and Parexochomus nigripennis (Coleoptera: Coccinellidae) were also recorded attacking the invasive mealybug.